Integrating family business values into cultural heritage stewardship at Malacca Heritage World Site, Malaysia - Ismail, Erwan; Abdullah Sani, Noorfathehah; Yusof, Yusnita; Abdul Rahman, Nuraini; Abu Bakar, Abu Yazid (Creative Publishing House, 2025)
This research investigates the intersection of family business practices and cultural heritage management in Malaysia, a country rich in cultural diversity and history. The study was motivated by the need to understand how family-run businesses contribute to preserving and promoting cultural heritage in Malaysia. Through a comprehensive qualitative approach, researchers examined the business strategies, cultural values, and operational models of family businesses engaged in cultural heritage sectors. The findings revealed a unique blend of traditional values and modern business understanding, highlighting how these businesses play a crucial role in sustaining cultural heritage. Family businesses in Malaysia have developed distinctive approaches to cultural heritage management, blending traditional values with innovative strategies to navigate the challenges of modernisation and globalisation. This has implications for business practices and cultural preservation, offering insights into sustainable cultural heritage management in a rapidly evolving global landscape. The study underscores the importance of family business-based culture in the stewardship of cultural heritage. It argues for greater recognition of these businesses in policy formulation and heritage management strategies. The “take home” message is clear: Malaysia's symbiotic relationship between family businesses and cultural heritage presents a unique model that balances economic viability with cultural preservation, offering valuable lessons for the business world and cultural heritage sectors globally.